Progression from isolated growth hormone deficiency to a combined pituitary hormone deficiency in a cohort of paediatrics patients with pituitary morphology abnormalities on MRI - Cristina Aguilar-Riera; Diego Yeste; Núria González-Llorens; Eduard Mogas; Ariadna Campos-Martorell; Paula Fernandez-Alvarez; Elida Vázquez; María Clemente (BMC Endocrine Disorders)
Abstract Objective To evaluate the baseline and follow-up clinical and radiological characteristics of a paediatric cohort initially diagnosed with isolated congenital growth hormone deficiency (IGHD) and pituitary morphology abnormality in MRI. Patients and methods Observational, ambispective and longitudinal review of paediatric patients with an initial diagnosis of growth hormone deficiency with pituitary morphology abnormality in MRI followed-up in a single tertiary hospital. Results After mean 11.3 (± 3.5DS) years of follow-up, the thirty patients (20 males) were classified into two groups: (1) isolated congenital growth hormone deficiency (IGHD) with 24 patients (9.5 years median follow up), and (2) combined pituitary hormone deficiencies (CPHD) with 6 patients (13.5 years median follow up). Median age at diagnosis was IGHD 3.0 [2.0–4.0] and CPHD 3.0 [1.5–5.2] years. Regarding the cerebral MRI scan results, 2 patients had septo-optic dysplasia (CPHD), 5 had pituitary stalk interruption syndrome (3 IGHD), one had ectopic posterior pituitary (IGHD), 16 had anterior pituitary hypoplasia (15 IGHD) and 6 had the latter two conditions combined (5 IGHD). In genetic studies, 1 of 25 patients had positive NGS panel results and it was in the IGHD group. The target gene detected was GLI2. Clinical exome sequencing was performed with six patients, yielding inconclusive results (1 in the IGHD group and 5 in the CPHD group). Array CGH was performed with eight patients (4 in the IGHD group and 4 in the CPHD group) and was negative in all patients. In the CPHD group, associated deficiencies begin to appear after 5 years [4.0–6.0] median follow-up, with thyrotropin being the most frequent (80%), followed by gonadotropin deficiency. ACTH and AVP deficiencies were less frequent. Conclusions Multiple hormone deficiencies were diagnosed during this cohort’s follow-up evaluation, whose first presentation was isolated growth hormone deficiency and pituitary morphology abnormality in MRI. Pathogenic gene variant involved in congenital hypopituitarism (GLI2) was found in one patient. Regular follow up of pituitary hormonal function in such patients is advisable due to the risk of new added deficiencies.